COMPARATIVE RESEARCH OF CUSTOMER VALUE PROPOSITION BETWEEN MALE AND FEMALE CUSTOMER OF INDOMIE PRODUCT - Rantung, Ryan .; Lapian, Joice .; Tumbuan, W.J.F Alfa (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract : This research aims to see if there is significant difference between Male and Female customers of Indomie Products based on Customer Value Proposition This research type is descriptive with quantitative method, using Independent Sample T-Test as analytical tool. The sample size of this research is 100 Customer divided to 50 Male and 50 Female as respondents. Simple Random Sampling was used to collecting data through questionnaire. The result shows that there is no significant difference based on Customer Value Proposition in Functional Value and Emotional Value while there is significant difference based on Customer Value Proposition in Economical Value and Symbolic Value between Male and Female customers. Future Recommendation for Indomie is Indomie Products should focus on giving their products more on Economic Value such as giving promotions, because Indomie is affordable yet high quality Instant Food products compare to other products. And also Indomie should give more meaning for people to buy their products, because as the result says that Symbolic Value had significant difference for people. Indomie can start doing recycling their product or use more healthy basic ingredients for their productsÂ Keywords: customer value proposition, independent sample t-test